Zeolitized volcanic ashes as supports for Anderson heteropolycompound catalysts. Application in the oxidation of diphenyl sulfide. (March 2023) - Muñoz, M.; Pereyra, A.M.; Gonzalez, M.R.; Monzón, J.D.; Romanelli, G.P.; Cabello, C.; Basaldella, E.I.
Abstract: This work proposes a new set of active catalysts in eco-compatible processes for the selective oxidation of aromatic sulfides. The applied methodology consists of improving the performance of the Anderson phases by dispersing them in low-cost supports. Starting from deposits of residual volcanic ash situated in the Argentine Patagonia area, novel supports containing high percentages of NaA or NaX zeolites were synthesized using a simple procedure that improves the ash reactivity towards the zeolite generation. These supports were impregnated with the Co(III)Mo6 Anderson phase and tested as heterogeneous catalysts in the clean oxidation of diphenyl sulfide with H2 O2 . The materials were characterized by XRD, FT-IR, SEM-EDX and Raman. The addition of CoMo6 to the obtained supports increased the conversion level from 50% to 60% to values greater than 90% in 90 min of reaction. The non-impregnated supports showed high selectivity towards diphenyl sulfoxide. Catalysts prepared from supports containing high percentages of zeolite A showed the best performance at short reaction times, while for extended times the highest conversions were obtained with the NaX- supports. The results allowed concluding that the innovative heterogeneous catalysts obtained showed a very good catalytic performance for the fast eco-compatible oxidation of diphenyl sulfides. Graphical Abstract: ga1 Highlights: Zeolites A and X were synthesized using a cost-effective procedure from volcanic ash. Dispersion of Anderson phases on low-cost supports improved the catalyst performance. A good catalytic performance for the oxidation of diphenyl sulfides was obtained.